ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI INITIAL RETURN SETELAH IPO DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Debi Carolina; Dwi Desy Miswati (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2021)
Initial Public Offering is a mechanism in which a company for first time issues new stock and is then offered to the public. The factors affecting the initials return are Return On Asset, Financial Leverage, and Earning Per Share. The problems with this research are (1) What is the development of return on asset, financial leverage, earning per share and initial return on non-financial firms registered in BEI? (2) How does return on asset, financial leverage, and earning per share affect the initials return partially? (3) How does return on asset, financial leverage, and earning per share affect the initials return simultaneously? The purposes of this research are (1) To find out the progression of return on asset, financial leverage, earning per share, and initial return. (2) To know the impact of return on asset, financial leverage, and earning per share toward the initial return partially. (3) To know the impact of return on asset, financial leverage, and earning per share toward the initial return simultaneously. Locus in this research is conducted on a company that did IPO and registered to the Indonesian Stock Exchange in 2017-2019. The number of peoples in this research are 145 companies, and the selection of samples was used by purposive sampling technique to 34 IPO companies listed in the Indonesian Stock Exchange as a research. The method of data analysis used is descriptive and verificative, where it makes classical assumptions and multiple linear regression tests. Simultaneous research reveals that there have been significant effects on initials return. And partial, financial leverage has a positive effect on the initials return. Whereas the return on asset and earning per share have no effect on initials return.